Improving Quality on Indonesia Curriculum Management: Reactualizing Total Quality Management as Methods: Meningkatkan Kualitas Manajemen Kurikulum di Indonesia: Reaktualisasi Manajemen Mutu Total sebagai Metode - Rahmanto, Muhammad Arifin; Ramadhan, Alif Rizky (Pedagogia : Jurnal Pendidikan, 2024)
This research is a analysis of some of the problems that arise in efforts to improve quality in curriculum management in Indonesia. Where, the system is still different between one region and another. Therefore, a concept that is deeply rooted and has proven its use in education is needed to be applied in Indonesia. So this paper offers TQM as a quality tool that can be used thoroughly in Indonesia. This research uses a qualitative approach with a descriptive-analytical approach. From the results of the paper, it can be concluded that the system developed by TQM can unify the methods of assessment and quality improvement in curriculum management. Highlights: Standardization: TQM facilitates uniformity in assessment and quality enhancement methods. Adaptability: TQM offers flexibility to accommodate diverse regional needs within a standardized framework. Systemic Integration: Implementing TQM can unify curriculum management practices across different regions in Indonesia. Keywords: Obstacle, Practicum, Science, Elementary School